KECEMASAN MATEMATIS SISWA DALAM PENERAPAN PEMBELAJARAN MATEMATIKA PADA KURIKULUM MERDEKA BELAJAR - Hajerina; Badjeber, Rafiq; Suciati, Indah; Manaf, Abdul (Koordinat Jurnal MIPA, 2023)
To describe students' mathematical anxiety in the application of learning mathematics to the independent learning curriculum, a qualitative descriptive study was conducted. To measure the level of students' mathematical anxiety, a math anxiety scale was used which was given to class VIIA students at SMP Alkhairaat 1 Palu. Based on the results of the instrument analysis, 3 students with high, medium and low abilities were selected as research subjects. The three subjects were interviewed to obtain further information needed in this study. To obtain answers to the formulation of the research problem, an interactive Miles & Huberman analysis was carried out and triangulation was carried out to obtain data validity. The findings obtained describe the four indicators of mathematical anxiety in class VIIA SMP Alkhairaat 1 Palu. From these findings the results show that 1) students' different math anxiety affects their way of learning, 2) differences in students' math anxiety levels are influenced by somatic aspects, knowledge aspects, affective aspects, and psychomotor aspects, (3) factors that influence level of math anxiety consists of personal factors and environmental factors